Diagnosis and Treatment of an Odontogenic Epithelial Tumor in a Dog With Features of Squamous Odontogenic Tumor. (June 2019) - Hodesson, Deborah L.; Soukup, Jason; Bell, Cynthia M.
A 9-year-old standard poodle presented for a comprehensive oral health assessment and treatment, at which time a left rostral mandibular swelling was recognized. The mass was biopsied and eventually excised by a left rostral mandibulectomy en bloc resection. Histopathology supported the diagnosis of a benign, intraosseous, epithelial tumor that was otherwise unclassified. The clinical, radiological, and histological features of this case are similar to those reported for squamous odontogenic tumor (SOT) in humans. This case study relays the diagnosis, treatment, and follow-up of the first SOT-like tumor in a dog.